2019
DOI: 10.6007/ijarafms/v8-i4/5471
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Deterrence Factors on Income Tax Evasion among Palestinian SMEs

Abstract: Tax evasion remains an issue confronting most policy makers worldwide. Palestine, as an evolving developing country highly depends on tax revenue and funds from international aids to finance the country's growth plan. The current study aims at examining relationships between probability of detection, tax penalty, tax rate and income tax evasion by applying the Deterrence Theory. A proportionate sampling technique was employed to collect data for the study through the use of questionnaires. The total number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 32 publications
3
26
2
Order By: Relevance
“…This implies that a 1% change in tax fairness keeping the other things remain constant can result in a change in taxpayers engage in tax evasion by .468% in the same direction. This result is similar to the finding of Majid et al (2017) and contradicts the finding of Alkhatib et al (2019) and Rantelangi and Majid (2018). Thus, the final model of the study would be: Tax evasion = .623 + .197MO + .174TK + .468TF To generalize, the standardized beta coefficient indicates that tax fairness highly affects taxpayers to engage in tax evasion by 56.3%, tax knowledge affects secondly taxpayers to engage in tax evasion by 18.3%, and moral obligation affects taxpayers to engage in tax evasion by 17.7%.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…This implies that a 1% change in tax fairness keeping the other things remain constant can result in a change in taxpayers engage in tax evasion by .468% in the same direction. This result is similar to the finding of Majid et al (2017) and contradicts the finding of Alkhatib et al (2019) and Rantelangi and Majid (2018). Thus, the final model of the study would be: Tax evasion = .623 + .197MO + .174TK + .468TF To generalize, the standardized beta coefficient indicates that tax fairness highly affects taxpayers to engage in tax evasion by 56.3%, tax knowledge affects secondly taxpayers to engage in tax evasion by 18.3%, and moral obligation affects taxpayers to engage in tax evasion by 17.7%.…”
Section: Discussionsupporting
confidence: 73%
“…The regression result indicates in Table 7 that tax fairness positively influences the taxpayers to engage in tax evasion. This result is similar to the finding of Majid et al, (2017) and contradicts with the finding of Rantelangi and Majid (2018) and Alkhatib et al (2019). Accordingly, the proposed hypothesis has been accepted because the beta value is .563 and the p value is less than .05.…”
Section: H 2 Tax Fairness Has a Positive Influence On Taxpayers To contrasting
confidence: 56%
See 2 more Smart Citations
“…Hence if the expected penalty is high when caught, the smaller the temptation into shadow economy will be (Virta, 2010). Similarly, it is established that the antecedents of tax evasion will surely have effect on shadow economies, therefore extant studies found that the penalty is negatively related with tax evasion (Alkhatib et al, 2018;Allingham and Sandmo, 1972;Chau and Leung, 2009;Feld and Frey, 2006;Hasseldine et al, 2007).…”
Section: Penalty Rate and Shadow Economy Levelmentioning
confidence: 98%